Assessing the Influence of Learning Styles, Instructional Strategies, and Assessment Methods on Student Engagement in College-Level Science Courses - Abdullah, Gamar; Arifin, Arifin; Saro’i, Mohammad; Uhai, Sabalius (PT. BATARI EDU CALYA, 2024)
In the realm of higher education, understanding the complex interplay among learning styles, instructional strategies, and assessment methods is crucial for fostering meaningful student engagement in college-level science courses. This research aims to fill a gap in existing literature by systematically examining the collective impact of these elements on student engagement. Employing a mixed-methods approach, the study involves quantitative surveys and qualitative interviews with both students and educators in diverse science disciplines. The research objectives include assessing prevalent learning styles, examining instructional strategies and assessment methods, analyzing their relationships, and gauging their impact on student engagement. The study's significance lies in contributing nuanced insights to science education and offering practical implications for educators to enhance pedagogical practices.